SOCIOLOGÍA DE LAS ORGANIZACIONES - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2009)
Abstract. One objetive is to approach to the reality of the social organizations, with particular emphasis in the conflicts and changed the economic organizations. The contemporary society is a community of organizations. These constitute forms of social, economic and political associations that have become indispensable obtaining important objectives for the human life. The contemporary society without considering the set of organizations cannot be understood who articulate the frame of their operation: educative, economic, political, religious, military, sport, playful, welfare institutions, etc. The satisfaction of the most basic necessities is obtained, by the relation with some of these organizations. Resumen. Se trata en este texto abordar la realidad de las organizaciones, con particular énfasis en los conflictos y cambiasen las organizaciones económicas. La sociedad contemporánea es una comunidad de organizaciones. Éstas constituyen formas de asociaciones sociales, económicas y políticas que se han convertido en indispensables para lograr objetivos importantes para la vida humana. No se puede entender la sociedad contemporánea sin considerar el conjunto de organizaciones que articulan el armazón de su funcionamiento: instituciones educativas, económicas, políticas, religiosas, militares, deportivas, lúdicas, asistenciales, etc. La satisfacción de las necesidades más básicas se logra, por la relación con algunas de estas organizaciones.